Inclusive Physical Education: Reviewing Policies, Practices, and Challenges - Srinivasan, J. P. Desiga (AG Volumes, 2025)
Global recognition has been accorded to inclusive physical education for its significance in promoting equity and participation among all students. However, there is still little study on this subject, especially in secondary schools. In this article review the various literature’s study on policies, practices, and challenges in physical education. This review highlight that inclusive physical education faces numerous challenges, including budget constraints, outdated curricula, inadequate teacher training, and limited student participation. These issues hinder the effective implementation of physical education in schools, especially in India. To ensure inclusivity, physical activities must be tailored to individual needs and capabilities, particularly for marginalized groups and students with disabilities. Teachers should assess students individually and adopt diverse instructional methods to foster meaningful participation. With proper training and updated practices, educators can help all students achieve key learning milestones. Promoting inclusivity in physical education ensures equal learning opportunities and supports holistic student development.